Health and Wellness Photovoice Project: Engaging Consumers With Serious Mental Illness in Health Care Interventions. (May 2013) - Cabassa, Leopoldo J.; Parcesepe, Angela; Nicasio, Andel; Baxter, Ellen; Tsemberis, Sam; Lewis-Fernández, Roberto
People with serious mental illnesses (SMI) are at increased risk for cardiovascular disease and premature mortality. We used photovoice in two supportive housing agencies to engage consumers with SMI to inform the implementation of health care interventions. Sixteen consumers participated in six weekly sessions in which they took photographs about their health and discussed the meanings of these photographs in individual interviews and group sessions. We identified several implementation themes related to consumers' preferences. Peer-based approaches were preferred more than clinician-driven models. Participants expressed a desire to learn practical skills through hands-on activities to modify health behaviors. Consumers expressed a desire to increase their physical activity. Participants revealed in their photographs and narratives the important role that communities' food environments play in shaping eating habits. In this article, we show how photovoice can generate valuable community knowledge to inform the translation of health care interventions in supportive housing agencies.